Identification of Single Nucleotide Polymorphism and Pathway Analysis of Apolipoprotein A5 (APOA5) Related to Fatty Acid Traits in Indonesian Sheep - Gunawan, A.; Anggrela, D.; Listyarini, K.; Abuzahra, M. A.; Jakaria, Jakaria; Yamin, M.; Inounu, I.; Sumantri, C. (Tropical Animal Science Journal, 2018)
This study was aimed to identify single nucleotide polymorphism (SNP) and pathway analysis of APOA5 with fatty acids traits in sheep. A total of 47 rams consisted of 20 heads of Javanese Fat Tailed (JFT), 17 heads of Javanese Thin Tailed (JTT), and 10 heads of Garut Composite Sheep (GCS) were used in this study. Fatty acids traits were measured at the age of 12 months with the average body weight of 25-30 kg. Identification of polymorphism of APOA5 (g.26929941 C>T) gene were analyzed using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP). The pathway analysis of APOA5 gene was performed using Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. The SNP of APOA5 gene were found polymorphic with three genotypes (CC, CT, and TT). The gene frequency of CC, CT, and TT were 0.83, 0.11, and 0.06, respectively. The chi square test revealed that the locus of APOA5 (g.26929941 C>T) was in Hardy-Weinberg equilibrium, except in thin tailed sheep. The chi-square values of JFT, JTT, and GCS were 0.05, 0.03, and 0.04, respectively. A SNP of APOA5 was associated (P